STUDYING THE FAMILY PSYCHOLOGICAL ENVIRONMENT IN SINGLE-PARENT FAMILIES - Babajanova Feruza Aminboyevna (The Conference Hub, 2025)
This thesis focuses on studying the psychological environment in single-parent families. The research analyzes the impact of family instability, parent relationships, and the psychological effects on children's development. Psychological issues such as stress, anxiety, and low self-esteem are prevalent among children raised in single-parent families. The aim of this study is to develop effective pedagogical approaches and provide psychological support for children growing up in single-parent families.
Keywords: Single-parent families, psychological environment, family instability, child psychology, parent relationships, psychological support, stress, anxiety, personal development.